In vitro Antitubercular Activity of Dihydropyridine-Dicarboxamide and Pyrazole Derivatives against Mycobacterium tuberculosis (Bulletin of Pure & Applied Sciences- Zoology, 2019)
The 1,4-dihydropyridine (DHP) is the most  feasible heterocyclic ring with various  substitutions at several positions. The DHP and  pyrazole are ever-growing due to their varied  biological, pharmaceutical and therapeutic  applications. The antitubercular activity of some  DHP and pyrozole derivatives (BPD, CMBPD,  NMBPD, DPD, DNDDP, DMDDP, BEMPMP,  OMEMPMP, KPEMPMP, CEMTDP and  NEPMCP) have been documented in the present  study. The in vitro activity of selected compounds  as antitubercular agents have been measured in  term of zone of inhibition (ZI) and minimum  inhibitory concentration value (MIC, MIC50 and  MIC90). The compounds BPD, DNDDP, CEMTDP,  NEPMCP showed good antitubercular activity  against Mycobacterium tuberculosis with zone of  inhibition 20-21mm and MIC value ranged  between 5-12. The other derivatives DPD,  CMBPD, OMEMPMP demonstrated moderate  antitubercular activity against M. tuberculosis  with zone of inhibition 14 to 17mm with MIC  value 10 to 14. However, compounds NMBPD,  DMDDP showed remarkable antitubercular  activity against M. tuberculosis with zone of  inhibition 21mm and MIC value 4-5. While the  compounds BEMPMP, KPEMPMP showed mild  activity against M. tuberculosis with zone of  inhibition 11-12mm and MIC value between 17- 20.